Development of Indonesian Language-Based Health Education Media to Improve Community Knowledge on Hypertension Prevention - Sabriadi, Ririn; Asrar As; Jusriani, Rini; Mukty, Ma’rifat Istiqa; Jaya, Arianti Indah (Universitas Islam Negeri Alauddin Makassar, 2025)
Hypertension is a non-communicable disease with a high prevalence and is a major risk factor for cardiovascular disease, stroke, and kidney failure. Low public knowledge regarding hypertension risk factors and prevention remains one of the barriers to effective disease control. The development of Indonesian-based health education media is needed to improve community health literacy through the delivery of easily understandable health information. This study employed a Research and Development (R&D) method to develop Indonesian-based health education media in the form of leaflets, posters, and digital infographics on hypertension prevention. The research stages included needs analysis, media design, development, expert validation, and community trials. Validation was conducted by content experts, media experts, and language experts using a Likert scale instrument. The effectiveness of the media was measured by assessing changes in knowledge using a pre-test and post-test design. The validation results showed that the developed educational media obtained an average feasibility score of 94.0%, categorized as highly feasible. The trial results demonstrated an improvement in community knowledge, with the proportion of respondents in the good knowledge category increasing from 35% to 80%, while the moderate and poor knowledge categories decreased. In conclusion, Indonesian-based health education media is effective in improving community knowledge regarding hypertension prevention and can be utilized as a community-based health promotion medium.